Discrepancies between Self- and Clinical Staff Members’ Perception of Cognitive Functioning among Patients with Schizophrenia Undergoing Long-Term Hospitalization - Fumiko Kaneko; Hitoshi Okamura (Occupational Therapy International)
In Japan, long-term hospitalization of patients with schizophrenia is still prevalent, even though the focus of psychiatric care is shifting from hospitals to the community. Difficulties in discharge planning often arise because clinical staff members’ functional assessment differs from that of patients’ self-assessment. Therefore, we attempted to identify characteristics related to these perceptual differences to promote the development of more effective approaches toward the discharge and societal reintegration of patients with schizophrenia undergoing prolonged hospitalization. Forty-eight long-term inpatients (23 men and 25 women with a mean age of 60.72 years) with schizophrenia were examined using the Schizophrenia Cognition Rating Scale Japanese version (SCoRS-J), Life Skills Profile (LSP), and Profile of Mood States- (POMS-) Brief Form. Differences between patients’ self-ratings and clinical staff members’ ratings on the SCoRS-J were used to divide patients into overestimators, underestimators, and accurate raters. These groups were then comparatively analyzed. Accordingly, overestimators displayed significantly severe cognitive dysfunction on the SCoRS-J objective ratings (p=.001) and significantly less difficulty on the SCoRS-J subjective ratings (p=.002) as compared to underestimators. Overestimators also scored significantly lower on the communication (p=.012) and responsibility (p=.021) LSP subscales compared to underestimators, and the total LSP score for overestimators was significantly lower compared to accurate raters (p=.036) and underestimators (p=.009). However, underestimators displayed significantly higher confusion on the titular POMS subscale than did overestimators (p=.021). These findings indicate that, among the three groups, overestimators scored lowest for objectively rated functioning. In contrast, underestimators attained the highest functioning; however, they were also confused. Clinical staff should examine how patients’ self-perceptions deviate from the perceptions of staff and implement an appropriate approach considering the patient characteristics revealed from the results of this study.